Parallel lines are equal to each other(congruent). the slope is 4
Answer:
<h2>f(x - k) = (x - k)²⇒ k = 5</h2>
Step-by-step explanation:
f(x) + n - shift the graph n units up
f(x) - n - shift the graph n units down
f(x - n) - shift the graph n units to the right
f(x + n) - shift the graph n units to the left
==============================================
Look at the picture.
The graph has been shifted 5 units to the right.
Therefore we have f(x - 5).
Step-by-step explanation:
we don't see the complex numbers.
so, we cannot check their distances.
a suspicion, though.
sqrt(45) a distance between 2 complex numbers is
sqrt(a² + b²).
so,
a² + b² = 45
a nice combination of whole square numbers would be 6 and 3.
6² + 3² = 36 + 9 = 45
if that is the case, then that would mean one of the following committed numbers
6 + 3i
3 + 6i
-6 + 3i
6 - 3i
-6 - 3i
-3 + 6i
3 - 6i
-3 - 6i
one of these numbers must be the result of the subtraction of the 2 provided complex numbers.
remember
(a + bi) - (c + di) = a-c + (b-d)i
Answer:
First number =26
Second number =49
Step-by-step explanation:
Question:
The sum of two numbers is 75. The second number is 3 less than twice the first. Find the numbers.
Given:
Sum of two numbers = 75
The second number is 3 less than twice the first.
To find the numbers.
Solution:
Let the first number be = ![x](https://tex.z-dn.net/?f=x)
Let second number be = ![y](https://tex.z-dn.net/?f=y)
The sum equation can be given as:
![x+y=75](https://tex.z-dn.net/?f=x%2By%3D75)
It is given that the second number is 3 less than twice the first.
This can be given as:
![y=2x-3](https://tex.z-dn.net/?f=y%3D2x-3)
Substituting the value of
in terms of
in the sum equation.
![x+(2x-3)=75](https://tex.z-dn.net/?f=x%2B%282x-3%29%3D75)
Combining like terms.
![3x-3=75](https://tex.z-dn.net/?f=3x-3%3D75)
Adding 3 both sides.
![3x-3+3=75+3](https://tex.z-dn.net/?f=3x-3%2B3%3D75%2B3)
![3x=78](https://tex.z-dn.net/?f=3x%3D78)
Dividing both ides by 3.
![\frac{3x}{3}=\frac{78}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%7D%7B3%7D%3D%5Cfrac%7B78%7D%7B3%7D)
![x=26](https://tex.z-dn.net/?f=x%3D26)
Substitution
in the second equation to find
.
![y=2(26)-3\\y=52-3\\\therefore y=49](https://tex.z-dn.net/?f=y%3D2%2826%29-3%5C%5Cy%3D52-3%5C%5C%5Ctherefore%20y%3D49)
Thus, first number =26 and second number =49.
Depends on what equation or question you want to be answered from the whole section of geometry...